Heterologous expression of family 10 xylanases from Acidothermus cellulolyticus enhances the exoproteome of Caldicellulosiruptor bescii and growth on xylan substrates. Issue 1 (December 2016) - Kim, Sun-Ki; Chung, Daehwan; Himmel, Michael; Bomble, Yannick; Westpheling, Janet
Abstract Background The ability to deconstruct plant biomass without conventional pretreatment has made members of the genusCaldicellulosiruptor the target of investigation for the consolidated processing of lignocellulosic biomass to biofuels and bioproducts. These Gram-positive bacteria are hyperthermophilic anaerobes and the most thermophilic cellulolytic organisms so far described. They use both C5 and C6 sugars simultaneously and have the ability to grow well on xylan, a major component of plant cell walls. This is an important advantage for their use to efficiently convert biomass at yields sufficient for an industrial process. For commodity chemicals, yield from substrate is perhaps the most important economic factor. In an attempt to improve even further the ability ofC. bescii to use xylan, we introduced two xylanases fromAcidothermus cellulolyticus . Acel_0180 includes tandem carbohydrate-binding modules (CBM2 and CBM3) located at the C-terminus, one of which, CBM2, is not present inC. bescii . Also, the sequences of Xyn10A and Acel_0180 have very little homology with the GH10 domains present inC. bescii . For these reasons, we selected these xylanases as potential candidates for synergistic interaction with those in theC. bescii exoproteome. Results Heterologous expression of two xylanases fromAcidothermus cellulolyticus inCaldicellulosiruptor bescii resulted in a modest, but significant increase in the activity of the exoproteome ofC. bescii on xylan substrates. Even though the increase in extracellular activity was modest, the ability ofC. bescii to grow on these substrates was dramatically improved suggesting that the xylan substrate/microbe interaction substantially increased deconstruction over the secreted free enzymes alone. Conclusions We anticipate that the ability to efficiently use xylan, a major component of plant cell walls for conversion of plant biomass to products of interest, will allow the conversion of renewable, sustainable, and inexpensive plant feedstocks to products at high yields.